Outcome of Concurrent Chemoradiotherapy versus Sequential Chemotherapy Followed by Radiotherapy for Limited Stage Small Cell Lung Cancer Treatment - Sultana, Suriana; Ali, Md Yousuf; Begum, Rowshon Ara; Mariam, Lubna; Siddiqua, Asma; Sultana, Mosammat Rubina; Sultana, Sarowat (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Background: Limited-stage small cell lung cancer (LS-SCLC) is a highly aggressive malignancy with poor prognosis. Concurrent chemo-radiotherapy (CCRT) is recommended by guidelines, but sequential chemotherapy followed by radiotherapy (SCRT) is often used in settings with resource limitations and afraid of intolerability. This study compares CCRT with SCRT in terms of clinical and radiological response, and treatment-related toxicities. Methods: This quasi-experimental prospective study included 60 histologically proven LS-SCLC patients at the National Institute of Cancer Research & Hospital, Dhaka, from July 2020 to June 2021. Patients were divided equally into two arms: Arm A received CCRT (60 Gy in 30 fractions via 3DCRT with concurrent EP chemotherapy), while Arm B received SCRT (4 cycles of EP followed by 60 Gy in 30 fractions via 3DCRT). Response evaluation was done after 12 weeks post-treatment by clinical and radiology using RECIST 1.1 criteria and RTOG toxicity grading. Results: Complete clinical response was higher in Arm A (86.7%) vs Arm B (80.0%). Radiological response was similar (86.7% vs 83.3%). Improvement in symptoms such as dyspnea (100% vs 100%), weight loss (63.3% vs 31.8%, p=0.039), and chest pain (61.5% vs 23.0%, p=0.016) was significantly better in Arm A. Toxicities were manageable; esophagitis (70.0% vs 63.3%) and radiation pneumonitis (43.3% vs 36.7%) were higher in Arm A but not statistically significant. Conclusion: In this series CCRT demonstrates noninferior clinical outcomes compared to SCRT in LS-SCLC, with comparable response rates and manageable toxicity. It remains a feasible treatment option for limited stage small cell lung cancer treatment. J Bangladesh Coll Phys Surg 2025; 43: 261-164